566 views
0 votes
I did try this problem out 5 times and I did put the -1 in for the x idk what I did wrong

I did try this problem out 5 times and I did put the -1 in for the x idk what I did-example-1
User Torben
by
5.3k points

2 Answers

6 votes

Answer:


\large\boxed{g(-1)=4}

Explanation:

In this question. we would be plugging in -1 to all of the x variables.

The equation we are solving is:


g(x)=(3x^2-2x+7)/(2x+5)

You would plug in -1 to all of the x variables.

Your equation should look like this:


g(x)=(3(-1)^2-2(-1)+7)/(2(-1)+5)

Now, you solve:


g(x)=(3(-1)^2-2(-1)+7)/(2(-1)+5)\\\\\text{Lets start with the top}\\\\g(x)=(3(1)-2(-1)+7)/(2(-1)+5)\\\\g(x)=(3-2(-1)+7)/(2(-1)+5)\\\\g(x)=(3+2+7)/(2(-1)+5)\\\\g(x)=(12)/(2(-1)+5)\\\\\text{We can do the bottom now}\\\\g(x)=(12)/(2(-1)+5)\\\\g(x)=(12)/(-2+5)\\\\g(x)=(12)/(3)\\\\\text{Divide the fraction}\\\\g(-1)=4

When you're done solving, you should get 4.

This means that when g is -1, the answer would be 4.

g(-1) = 4

I hope this helped you out.

Good luck on your academics.

Have a fantastic day!

User Javiera
by
5.8k points
6 votes

g(x)=3x^2-2(x+7)/2x+5

g(-1)=3(-1)^2-2(-1)+7/2(-1)+5

Do the numerator first

(3)(-1)(-1)-2(-1)+7

3+2+7

=12

2(-1)+5

-2+5

=3

Numerator= 12 , Denominator=3

Numerator/ Denominator = 12/3=4

Answer: g(-1)=4

User Secretive
by
4.9k points